2017
DOI: 10.18805/ijar.v0iof.7266
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations in reproductive parameters ofOuled Djellal rams in the East of Algeria

Abstract: This experiment was carried out on Ouled Djellal rams in order to study the effect of season on testicular size, serum testosterone level and semen characteristics for a period of one year. Blood samples were obtained via jugular vein, and semen was collected by using an electro-ejaculator from six fertile male rams (2-4 years of age) on a monthly basis. In this breed, testis parameters varied seasonally showing the highest average values during autumn. However, the variation of body weight, GSI, serum testost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
4
6
0
Order By: Relevance
“…Regarding HOST, the present findings are comparable with findings of Kaimal (2015) in NARI Suwarna rams with no seasonal variation but contradictory to Ntemka et al, (2019) with reported seasonal variation for sperm viability in Chios rams. Regarding sperm concentration and acrosome integrity, the present study is consistent with in Awassi rams observing no variations between the seasons for both these parameters while for sperm concentration only with other workers (Kaimal 2015;Belkhiri et al, 2017;Benmoula et al, 2017;Ntemka et al, 2019). Further, in complete contrast to the present study, Azawi and Ismaeel (2012) reported seasonal variations with lower sperm concentration and viability with higher acrosomal damages during winter in Awassi rams.…”
Section: Sperm Concentration Live Sperm Plasma Membrane Integrity and Acrosome Integritysupporting
confidence: 89%
See 1 more Smart Citation
“…Regarding HOST, the present findings are comparable with findings of Kaimal (2015) in NARI Suwarna rams with no seasonal variation but contradictory to Ntemka et al, (2019) with reported seasonal variation for sperm viability in Chios rams. Regarding sperm concentration and acrosome integrity, the present study is consistent with in Awassi rams observing no variations between the seasons for both these parameters while for sperm concentration only with other workers (Kaimal 2015;Belkhiri et al, 2017;Benmoula et al, 2017;Ntemka et al, 2019). Further, in complete contrast to the present study, Azawi and Ismaeel (2012) reported seasonal variations with lower sperm concentration and viability with higher acrosomal damages during winter in Awassi rams.…”
Section: Sperm Concentration Live Sperm Plasma Membrane Integrity and Acrosome Integritysupporting
confidence: 89%
“…Similar seasonal variations were also reported for volume, wave motion and individual motility in Dorper (Malejane et al, 2014), Naimi and Najdi rams (Al-Anazi et al, 2017). Further, some studies have reported seasonal variations for volume but not for wave motion and individual motility (Milczewski et al, 2015;Belkhiri et al, 2017) whereas, other studies have reported seasonal variations for wave motion and individual motility but not for semen volume (Chella et al, 2017).…”
Section: Volume Colour Wave Motion and Individual Motilitysupporting
confidence: 67%
“…Mean values of scrotal circumference, testicular volume, testicular width, and testicular length were significantly higher in autumn than those in winter. Authors in previous studies found a similar significant effect for the season on the testicular measurements [ 32 , 33 , 34 ]. Level of nutrition, daily body growth, and the response of the pineal gland to the day length are the main factors that affect testicular measurements [ 33 ].…”
Section: Resultssupporting
confidence: 63%
“…In evaluating rams for use in breeding, physical examination, measurements of genital tract and semen analysis are imperative (Hassani et al, 2014;Ridler et al, 2012;Alkawmani et al, 2018;2020;Belkhiri et al, 2019). An important measurement taken during the breeding sound examination of rams is the scrotal circumference (SC).…”
Section: Introductionmentioning
confidence: 99%